Analysis of the readiness of schoolchildren who participated in the regional stage of the All-Russian Olympiad in Physical Education - Bazilevich, M.V.; Dmitrieva, S.V.; Kotova, T.G.; Simonova, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse the outcomes of the theoretical-methodological test at the regional stage of the All-Russian Olympiad of schoolchildren of the Tyumen Region for the period from 2021 to 2025. Methods and structure of the study. In the period from 2021 to 2025, 1012 schoolchildren (9-11 grades) took part in the regional stage, of whom 48.7% (493) were female and 51.2% (519) were male. Results and conclusions. The average score in the theoretical-methodological test during this period did not rise above 6.9 points among the girls and 6.7 among the boys out of 20 possible. It was noted that the participants most successfully cope with closed-type questions and matching tasks. And the greatest difficulty for the participants, as a rule, is caused by open-type questions, tasks requiring knowledge of terminology in the description of physical exercises, as well as problem-solving tasks. The preparation of schoolchildren for participation in the All-Russian Olympiad should be regular, clearly thought out, and include the consideration of such topics as: the cultural-historical foundations of physical culture and sports, the foundations of the theory and methodology of teaching motor actions, the development of physical qualities, the rules of competitions in various sports, the conceptual apparatus in the field of physical culture and sports.